Diabetes Mellitus Among Adults in Herat, Afghanistan: A Cross-Sectional Study - Khwaja Mir Islam Saeed (University Library System, University of Pittsburgh, 2017)
Introduction: Diabetes is reaching epidemic levels in Afghanistan. This study identifies the risk factors associated with diabetes in Herat City, Afghanistan, and explores the prevalence of previously undiagnosed diabetes. Methods: A cross-sectional study was conducted using multistage cluster sampling by adopting the World Health Organization's (WHO) STEPwise approach to Surveillance (STEPS). We enrolled 1129 participants aged 25-70 years between May and June of 2015 (47.4% males, 52.6% females). A structured questionnaire was used for data collection of demographic, socioeconomic, and behavioral factors. Investigators collected anthropometric measurements and blood samples from study participants. A multivariable logistic regression model was used to identify factors associated with diabetes prevalence. Results: We found that the prevalence of diabetes in Herat City was 9.9% (9.8% in males and 10.1% in females). Of the 1129 respondents, only 3.3% were previously diagnosed with diabetes or were under treatment, whereas 6.6% of respondents were previously undiagnosed. The multivariable analyses showed that age, frequency of rice consumption, type of cooking oil, and systolic blood pressure were associated with diabetes.  Conclusions: This is one of the first studies to discuss the high prevalence of undiagnosed diabetes in Herat, Afghanistan. This study found several modifiable factors that were associated with diabetes in Herat, Afghanistan. Future reduction of disease burden should focus on these factors in the development of the most optimal diabetes prevention programs.